Re-description of Cephalobus topali Andrássy, 1970 (Rhabditida, Cephalobidae) from Vietnam, and transfer to Acrobeloides (Cobb, 1924) Thorne, 1937 - Nguyen, Thi Anh Duong; Bonkowski, Michael; Peña-Santiago, Reyes; Abolafia, Joaquín (Zootaxa, 2016)
Recently, specimens of Cephalobus topali, collected from an agricultural area from northern Vietnam, are described, including SEM study. They are characterized by their its 306–347 µm long body in females, lateral field with two alae or 3-4 longitudinal incisures, lip region with three pairs of asymmetrical conoid lips, three low and rounded labial probolae separate from the corresponding pair of lips by an incisure, U-shaped primary axils without guard processes, V-shaped secondary axils without guard processes, pharyngeal corpus slightly fusiform and 2.6–3.1 times the isthmus length, spermatheca and postvulval sac poorly developed, female tail conoid (18–24 µm, c = 12.7–17.0, c’ = 1.8–2.7) with rounded terminus ending in an acute or wart-shaped mucro, phasmid at 29–34% of tail length, and male unknown. SEM pictures reveal that lip region pattern significantly differs from that found in members of Cephalobus and fits that observed in Acrobeloides, so that the species is transferred to this genus. Cephalobus quadrilineatus is provisionally maintained as different from C. topali.